A Case of Metastatic Cutaneous Tubercular Abscess with Concomitant Central Nervous System Tuberculoma in an Indian Adolescent Girl - Reshma Joseph; Menaka P Nallasivam; Sasikumar B Raman (Pediatric Infectious Disease)
Cutaneous tuberculosis is a rare form of extrapulmonary tuberculosis, most commonly reported in high-prevalence countries like India. The diagnosis of cutaneous tuberculosis is challenging because of the paucibacillary nature of the disease, its rare occurrence, and its similarities with other cutaneous infections. It is characterized by a spectrum of distinct clinical and histopathological presentations, with underlying systemic involvement in most cases. Hence, awareness among clinicians of various cutaneous presentations of tuberculosis is crucial for early diagnosis and management. A thorough evaluation to identify the systemic focus is important, as it helps in determining the duration of therapy. The author herein presents a case of cutaneous tuberculosis presenting as multiple tubercular abscesses with concomitant central nervous system (CNS) tuberculoma in an adolescent girl.